Pengaruh Profitabilitas, Leverage, dan Struktur Modal terhadap Nilai Perusahaan dengan Kebijakan Deviden sebagai Variabel Moderasi - Nurul Rizki Yanti; Agrianti Komalasari; Kiagus Andi (Penerbit Goodwood, 2022)
Purpose: The COVID-19 epidemic has had a devastating impact on the international economy, particularly in Indonesia. The hospitality, dining, and tourism sectors are some of those most impacted by the COVID-19 pandemic. The impact of profitability, leverage, capital structure, and dividend policy as moderating variables on firm value is investigated in this study for companies in the hotel, restaurant, and tourism sub-sector listed on the Indonesian stock exchange between 2016 and 2021. Method: With data from the Indonesian stock exchange from 2016 to 2021, comparative descriptive approaches and quantitative methodologies were employed in this study. Purposive sampling was used to sample, and it revealed 15 businesses that fit the bill. Results: The findings in 15 companies show that profitability has no effect on firm value, with a significance value of 0,584; leverage has no effect on firm value, with a significance value of 0,896; capital structure has no effect on firm value, with a significance value of 0,122; dividend policy is able to moderate profitability on firm value, with a significance value of 0,025; dividend policy is unable to moderate the effect of leverage; and capital structure has no effect on firm value. Limitations: This study only uses the variables of profitability, leverage, capital structure, dividend policy to explain the variable value of the company, with a sample of companies in the hotel, restaurant and tourism sub-sector listed on the Indonesian stock exchange during 2016-2021. Contribution: The results of this study will likely be applied in investment decision-making. Businesses with concerns about profitability, debt, and capital structure can also utilize this research's findings as knowledge so they can act right away to keep their operations going in the future.